A dual‐band dual‐mode microstrip Yagi antenna with quasi‐end‐fire radiation. Issue 4 (6th January 2020) - Shi, Jiaqi; Zhu, Lei; Liu, Neng‐Wu; Wu, Wen
Abstract: A dual‐band dual‐mode microstrip Yagi antenna with quasi‐end‐fire radiation patterns is proposed in this paper. It consists of five radiating patches driven by a single slot‐loaded patch placed in the middle. Meanwhile, two slot‐loaded parasitic patches are symmetrically located on two sides of the driven patch, respectively. In the lower band, the five patches involved resonate at TM01 mode. While in the upper band, all the patches resonate at TM02 mode. In order to ensure quasi‐end‐fire radiations in the both bands, four slots are symmetrically etched around the strongest surface currents of each patch resonating at TM02 mode. As a result, the resonant frequency of TM02 mode is decreased dramatically, while the resonant frequency of TM01 mode almost remains unchanged. With these arrangements, the separations between any two of the adjacent patches at their centers satisfy the requirements in design of the microstrip Yagi antenna in both bands, so as to realize the dual‐band dual‐mode microstrip Yagi antenna on a single‐layer substrate. Finally, an antenna prototype is fabricated and tested. The measured results reveal that the dual operating bands of 2.76~2.88 and 4.88~5.03 GHz for |S11 | < −10 dB are satisfactorily achieved. Most importantly, the proposed antenna can indeed realize the quasi‐end‐fire radiation patterns in dual operating bands.